2002
DOI: 10.1046/j.1528-1157.43.s.5.18.x
|View full text |Cite
|
Sign up to set email alerts
|

Short‐Term Effects of Pilocarpine on Rat Hippocampal Neurons in Culture

Abstract: Summary:Purpose: Status epilepticus (SE) has been considered an epileptogenic factor in humans. In the pilocarpine (PILO) model, after a brief period marked by SE, the rats exhibit recurrent spontaneous seizures, mimicking the clinical features of temporal lobe epilepsy. The aim of our study was to identify the molecular actions of PILO that could account for its ability to induce SE.Methods: Whole-cell mode of the patch-clamp technique was applied to cultured hippocampal neurons (2-3 weeks old) in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 24 publications
0
16
0
2
Order By: Relevance
“…3). It has recently been demonstrated that, in presence of 1 to 10 \iM pilocarpine, cultured hippocampal neurones suffer an imbalance between inhibitory and excitatory transmission, which could be involved in the generation of repetitive seizures observed in rats during the acute phase of the pilocarpine model of epilepsy (Priel and Albuquerque, 2002). Unfortunately, no comparable information is available yet, regarding neocortical neurones.…”
Section: Discussionmentioning
confidence: 99%
“…3). It has recently been demonstrated that, in presence of 1 to 10 \iM pilocarpine, cultured hippocampal neurones suffer an imbalance between inhibitory and excitatory transmission, which could be involved in the generation of repetitive seizures observed in rats during the acute phase of the pilocarpine model of epilepsy (Priel and Albuquerque, 2002). Unfortunately, no comparable information is available yet, regarding neocortical neurones.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, muscarinic acetylcholine receptor receptor 1 (M 1 ) was shown to be important for development of seizures, since mice lacking this receptor failed to develop seizures following pilocarpine injection (Hamilton et al, ). Downstream of M 1 receptor activation, the homeostatic balance of neuronal excitation–inhibition is tipped toward increased excitability presumably at least in part by increase in glutamate release and sustained NMDA receptor activation (Priel and Albuquerque, ; Smolders et al, ). Although beyond the scope of this review, further details of the mechanics and precise pathological features of these models can be found in several excellent reviews of the kainic acid and pilocarpine models of experimental seizures/epilepsy (Curia et al, ; Levesque and Avoli, ; Levesque et al, ; Turski et al, ).…”
Section: Epilepsy: a Global Neurological Disordermentioning
confidence: 99%
“…After the initial period of SE, there is a “latent period” during which significant neural reorganization occurs followed by chronic life-long susceptibility to spontaneous, recurrent seizures (Cavalheiro et al, 1996; Curia et al, 2008; Müller et al, 2009; Perez-Mendes et al, 2011; Turski et al, 1989, 1984, 1983). The maintenance and generalization of SE and the development of spontaneous recurrent seizures (SRS) is thought to occur through hyperglutamatergic activity via NMDA receptors in the hippocampus (Nagao et al, 1996; Priel and Albuquerque, 2002; Smolders et al, 1997). Therefore, pilocarpine administration in wild-type mice provides the opportunity to assess novel therapies that interfere with excessive glutamate signaling.…”
Section: 1 Introductionmentioning
confidence: 99%